2014
DOI: 10.1016/j.jfma.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive hyperbaric oxygen therapy provides better effects on brain inflammation and oxidative damage in rats with focal cerebral ischemia

Abstract: The results provide the apparently contradictory finding that heightened oxygen tension reduced oxidative stress (and inflammation), which was reflected by increased antioxidant and decreased oxidant contents under focal cerebral ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…The animals were placed in hyperbaric chambers as previously described [10]. Then, the pressure was increased to 0.25 MPa at a rate of 100 kPa per min, and each treatment lasted for 60 min.…”
Section: Hyperbaric Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were placed in hyperbaric chambers as previously described [10]. Then, the pressure was increased to 0.25 MPa at a rate of 100 kPa per min, and each treatment lasted for 60 min.…”
Section: Hyperbaric Therapiesmentioning
confidence: 99%
“…Increasing evidence suggests that superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and catalase activity are increased after repeated HBO treatments [9,10], although some reports show that HBO treatment may cause excessive generation of ROS, which induces neuronal cell damage [2]. On the other hand, HBO therapy attenuates hypoxia in affected tissues, which is helpful for the protection of neuronal function.…”
Section: Introductionmentioning
confidence: 99%
“…The use of silymarin may therefore be considered a novel therapeutic strategy for protection against lung I/R injury. Animal and clinical trials have confirmed that the inflammatory response is focal to continuing tissue damage following cerebral ischemia, and this is observed to a greater degree following lung I/R injury (14,15). Reduction in the inflammatory response is therefore an important strategy to attenuate lung I/R injury.…”
mentioning
confidence: 99%
“…A large number of experimental studies have shown that changing the oxygen pressure in the body can greatly affect macrophage function . Hyperbaric oxygen therapy (HBOT), which is widely used, is the most representative example.…”
Section: Exogenous Inducers Of Macrophage Heterogeneitymentioning
confidence: 99%